2017
DOI: 10.1186/s12883-017-0914-2
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and metabolic syndrome in patients with multiple sclerosis from Asturias and Catalonia, Spain

Abstract: BackgroundThe impact of comorbidity on multiple sclerosis (MS) is a new area of interest. Limited data on the risk factors of metabolic syndrome (MetS) is currently available. The aim of this study was to estimate the presence of comorbid conditions and MetS in a sample of adult patients with MS.MethodsA retrospective, cohort study was conducted using electronic medical records from 19 primary care centres in Catalonia and Asturias, Spain. The number of chronic diseases (diagnoses), the Charlson Comorbidity In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 33 publications
3
28
1
11
Order By: Relevance
“…A considerable percentage of patients with hyperlipidaemia, especially with an elevated total cholesterol and LDL fraction, were observed in the studied group. The literature on the subject contains information regarding the negative influence of high cholesterol and triglyceride concentrations and the positive influence of an elevated HDL fraction on acute inflammatory activity [6]. Niektóre badania sugerują, że choroby współistniejące, takie jak choroby sercowo-naczyniowe, mogą przyspieszyć progresję niepełnosprawności u pacjentów z SM [7].…”
Section: Discussionunclassified
“…A considerable percentage of patients with hyperlipidaemia, especially with an elevated total cholesterol and LDL fraction, were observed in the studied group. The literature on the subject contains information regarding the negative influence of high cholesterol and triglyceride concentrations and the positive influence of an elevated HDL fraction on acute inflammatory activity [6]. Niektóre badania sugerują, że choroby współistniejące, takie jak choroby sercowo-naczyniowe, mogą przyspieszyć progresję niepełnosprawności u pacjentów z SM [7].…”
Section: Discussionunclassified
“…However, they are more or less likely to have been diagnosed with rheumatoid arthritis, lupus, psoriasis or type 1 diabetes . Other studies showed an association of ischemic heart disease, fibromyalgia, metabolic syndromes and epilepsy in the MS population compared with the general population . Mortality EMR‐based studies showed that the initial presentation by MS type (progressive MS), higher level of disability, and associated motor, sensory and cerebellar concerns are significant predictors of MS‐related mortality in a cohort of USA veterans, and suggested that MS survival is also influenced by patient comorbidities and lifestyles factors in addition to autoimmune processes .…”
Section: Use Of Electronic Medical Records In Multiple Sclerosis Resementioning
confidence: 99%
“…8 Other studies showed an association of ischemic heart disease, fibromyalgia, metabolic syndromes and epilepsy in the MS population compared with the general population. [9][10][11][12] Mortality EMR-based studies showed that the initial presentation by MS type (progressive MS), higher level of disability, and associated motor, sensory and cerebellar concerns are significant predictors of MS-related mortality in a cohort of USA veterans, 13 and suggested that MS survival is also influenced by patient comorbidities and lifestyles factors in addition to autoimmune processes. 14 Demographics data stored in EMR enabled researchers to also study differences in the incidence or prevalence of MS over time, or among different populations based on ethnicity, sex or geographic location.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…MS patients have increased cardiovascular risk even in the absence of traditional risk factors such as obesity, hypertension, type 2 diabetes or dyslipidemia suggesting disease-related factors contribute to the development of atherosclerosis in MS [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%